Mean-Field Approach to Dielectric Relaxation in Giant Dielectric Constant Perovskite Ceramics. (25th September 2013) - Ke, Shanming; Lin, Peng; Huang, Haitao; Fan, Huiqing; Zeng, Xierong
Abstract : The dielectric properties of CaCu3 Ti4 O3 (CCTO) and A2 FeNbO6 (AFN, A = Ba, Sr, and Ca) giant dielectric constant ceramics were investigated in the frequency range from 1 Hz to 10 MHz. The relaxation properties can be perfectly described by a polaron model, indicating that the dielectric relaxation is intimately related to the hopping motion caused by localized charge carriers.